The Emerging Potential of Microgrids in the Transition to 100% Renewable Energy Systems - Richard Wallsgrove; Jisuk Woo; Jae-Hyup Lee; Lorraine Akiba (Energies, 2021)
International, national, and subnational laws and policies call for rapidly decarbonizing energy systems around the globe. This effort relies heavily on renewable electricity and calls for a transition that is: (i) flexible enough to accommodate existing and new electricity end uses and users; (ii) resilient in response to climate change and other threats to electricity infrastructure; (iii) cost-effective in comparison to alternatives; and (iv) just in the face of energy systems that are often the result of—or the cause of—procedural, distributive, and historical injustices. Acknowledging the intertwined roles of technology and policy, this work provides a cross-disciplinary review of how microgrids may contribute to renewable electricity systems that are flexible, resilient, cost-effective, and just (including illustrative examples from Korea, California, New York, the European Union, and elsewhere). Following this review of generalized microgrid characteristics, we more closely examine the role and potential of microgrids in two United States jurisdictions that have adopted 100% renewable electricity standards (Hawai‘i and Puerto Rico), and which are actively developing regulatory regimes putatively designed to enable renewable microgrids. Collectively, this review shows that although microgrids have the potential to support the transition to 100% renewable electricity in a variety of ways, the emerging policy structures require substantial further development to operationalize that potential. We conclude that unresolved fundamental policy tensions arise from justice considerations, such as how to distribute the benefits and burdens of microgrid infrastructure, rather than from technical questions about microgrid topologies and operating characteristics. Nonetheless, technical and quantitative future research will be necessary to assist regulators as they develop microgrid policies. In particular, there is a need to develop socio–techno–economic analyses of cost-effectiveness, which consider a broad range of potential benefits and costs.